ρπ Puzzle: Its Perspectives and Possibilities : ρπ Puzzle: Its Perspectives and Possibilities - Younas, Farzana; Saeed, Khadija; Amin, Aneela; Islam, Ghalib ul (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
In order to understand Charmonium Physics there are much theoretical explanations on “ρπ puzzle” of Charmonium decays with a comparative study of theoretical concepts and experimental data. “ρπ puzzle” is the violation of the 12% rule satisfied by most of the hadronic decay modes. In this paper, experimental and theoretical perspectives and possibilities are reviewed. Charmonium decay into light hadrons is a rich source of information about strong interactions between quarks and gluons. Flavor change in c ̅ is an ideal case to study light hadron spectroscopy to probe their gluon contents and flavor. In order to understand Charmodynamics and the mysterious “ρπ puzzle” systematic, theoretical, experimental as well as concrete phenomenological knowledge is presented.Final state interaction, suppressed and enhanced hypothesis always play leading role to answer this question. Exploration of “ρπ puzzle” will be an expedition for opening new worlds of hadron phenomenology and a great scientific triumph for the pedestrians and scientists of high energy physics. For future developments, it is much urgent to construct new phenomenology, systematic measurements in charmonium decays are needed to answer “ρπ puzzle”. In this context, a large expected data of CLEO-c and BESIII will open a new era of charmodynamics will give a profound understanding of “ρπ puzzle”.